Model Kinerja Ekspor Industri Tekstil dan Produk Tekstil di Jawa Tengah - Aryanto, Vincent Didiek Wiet (Jurnal Widya Manajemen & Akuntansi, 2004)
This study focus The Export Performance Model of Textile and Apparel Products in Central Java, aimed at developing a model of export performance of textile and apparel products in Central Java. Based on the previous studies, therefore, export stimuli, export barriers, the source and use of information, organization knowledge were proposed as construct variables of this study.